Pemberdayaan Remaja Putus Sekolah Untuk Meningkatkan Kemandirian Melalui Tata Boga Di Panti Sosial Bina Remaja Taruna Jaya 1 - Cindy Tharisca Sukma (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The phenomenon of adolescents dropping out of school from year to year is still common and many are found to be the main factor caused by economic problems, therefore the increasing number of dropouts and neglected adolescents created social institutions to accommodate or accommodate people who really need and undergo empowerment. The place of research implementation is the Taruna Jaya 1 Tebet Youth Development Social Institution, South Jakarta. The purpose of this study was to determine the implementation of empowerment implemented by PSBR and to find out how culinary skills can increase the independence of adolescents who drop out of school. The type of research used is qualitative by collecting data in the form of interviews, observation, and documentation. The results of this study are in the form of independence through culinary skills experienced by teenage dropouts who have undergone a rehabilitation period at the Youth Development Social Center. The conclusion of this study is that the empowerment carried out by Bina Remaja Social Institution to accommodate socially troubled adolescents, especially adolescents who drop out of school, is very good and in accordance with the objectives. Suggestions for Catering Skills are to build more cooperation with outside parties so that the program runs optimally.